Wolf howls encode both sender- and context-specific information. (November 2018) - Watson, Stuart K.; Townsend, Simon W.; Range, Friederike
Abstract : Loud, long-distance calls serve varied functions across animal species including marking territory, attracting mates and signalling one's identity. Here, we examined the types of sender- and context-specific information encoded in the howls of captive timber wolves, Canis lupus . We analysed 913 howls from nine individuals across three packs and investigated whether howl structure varied consistently as a function of phenotypic factors (age class, sex, pack and identity of the caller) in addition to the context in which the call was produced: specifically, whether the call was produced in a 'spontaneous' context just after sunrise or was 'elicited' by the absence of a group member. Calls were correctly classified by individual identity and production context, but not by any other factors. Principal components analyses indicated that individual differences were primarily associated with frequency-based measures, whereas acoustic variation between production contexts was associated with a variety of frequency-, intensity- and energy-based measures. Recognition of individual differences in vocalizations is likely to be important for navigating social relationships in wolves and further work is required to determine which life history factors may shape these individual differences. Differences resulting from production context are suggestive that these howl variants may serve different functions. The extent to which these individual and contextual differences are understood by receivers remains an open question. Highlights: We examined the information encoded in the acoustic structure of timber wolf howls. Factors tested were identity, age class, sex, pack membership and behavioural context. Acoustic structure of howls varied as a function of identity and production context. Our approach highlights the complexity of social carnivores' vocal repertoires.